Development of an engineering model for predicting the transverse coefficients of thermal expansion of unidirectional fiber reinforced composites - Dong, Chensong (ASME International, 2009)
The coefficients of thermal expansion (CTEs) of fiber reinforced composites play animportant role in the design and analysis of composite structures. Since the thermalexpansion coefficients of polymer matrix materials are typically much higher than thoseof fibers, and the fiber often exhibits anisotropic thermal and mechanical properties, thestress induced in the composite due to temperature change is very complex. Large discrepanciesexist among the analytical models for the transverse CTE of unidirectionalcomposites. Hence, it is problematic when choosing a suitable model. With the developmentof computer technologies, finite element analysis (FEA) proved its effectiveness incalculating the effective CTE of composites. In this study, the transverse CTEs of unidirectionalcarbon fiber composites were calculated by finite element analysis using arepresentative unit cell. The analytical micromechanical models from literature werecompared against the FEA data. It shows that Hashin’s concentric cylinder model is thebest. However, it is inconvenient for practical applications due to the amount of computation.In this study, based on the FEA data, an engineering model for predicting thetransverse CTE of unidirectional composites was developed by regression analysis. This model was validated against the FEA and experimental data. It shows that the developed model provides a simple and accurate approach to calculate the transverse CTE of unidirectional composites.